(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Takecallis arundinariae and T. taiwanus are the most widespread aphids in bamboo nurseries in Lombardy. Field observations were carried out on Phyllostachis bambusoides on different stages and on mean fecundity; seasonal abundance has been studied for three years. T. arundinariae youngs has a mean life of 7,3 days, nymphs of 4,9 and adults of 62,4. The reproductive period lasts 57,5 days and fecundity is 151,4 youngs per female. T. taiwanus youngs has a mean life of 10,7 days, nymphs of 4,9 and adults of 65,8. The reproductive period lasts 61,7 days and fecundity is 105,7 youngs per female. The first species develops from February to the end of May, the second one from the beginning of May to the first days of August.